TRANEXAMIC ACID IN PEDIATRIC CARDIAC SURGERY: A COMPREHENSIVE REVIEW OF EFFICACY, SAFETY, AND CURRENT CONTROVERSIES - Michał Bereza; Mateusz Dembiński; Julia Prabucka-Marciniak; Edyta Szymańska; Joanna Kaszczewska; Patrycja Fiertek; Aleksandra Misarko; Zuzanna Burkacka; Jakub Pysiewicz; Kacper Kmieć (International Journal of Innovative Technologies in Social Science, 2025)
Pediatric patients undergoing cardiac surgery, particularly with cardiopulmonary bypass (CPB), are at high risk for significant bleeding and allogeneic blood transfusions due to their unique hemostatic profile. Tranexamic acid (TXA) is the primary antifibrinolytic agent used to mitigate this risk, but its efficacy, safety, and optimal administration in this population remain topics of debate. This article provides a comprehensive review and to synthesize the available evidence and identify critical knowledge gaps. Our analysis confirms that TXA significantly reduces postoperative blood loss and the need for allogeneic red blood cell and fresh frozen plasma transfusions. This effect was particularly notable in high-risk subgroups such as infants and cyanotic patients. Substantial heterogeneity was found across studies, primarily related to varying TXA dosing regimens and differing transfusion protocols, which limited the ability to define a single optimal dose. TXA is an effective agent for reducing bleeding and transfusion needs in pediatric cardiac surgery, but its use is associated with a potential, dose-dependent risk of seizures. The wide variability in dosing regimens and the lack of robust data on long-term neurological outcomes highlight a critical need for future large-scale, prospective trials. These studies should aim to standardize dosing protocols and definitively assess the true benefit-to-risk ratio of TXA in specific pediatric subgroups.